If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 2(y + -3) Reorder the terms: 5y = 2(-3 + y) 5y = (-3 * 2 + y * 2) 5y = (-6 + 2y) Solving 5y = -6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 5y + -2y = -6 + 2y + -2y Combine like terms: 5y + -2y = 3y 3y = -6 + 2y + -2y Combine like terms: 2y + -2y = 0 3y = -6 + 0 3y = -6 Divide each side by '3'. y = -2 Simplifying y = -2
| 8+5n-3=9n+13-6n | | -4+12=4b-1-3b | | -7.3x=43.8 | | 37x+17=6(6x+17) | | -37=-7+5w | | y=25+7x | | 4(a-3)=-2 | | -14+x=10 | | 8+3(3n+6)-n= | | 8x-(2x+8)=28 | | 3u-2=-23 | | 20=-6x+2x | | 7x+2(3x-1)=11 | | 8y+18=3y-2 | | -3+6=15 | | 5x=-32 | | 3m-5=8(6+5m) | | X^21-25X+24=0 | | 18x+y-4x+18y= | | 10x-15=7x | | 1.7q-3.8-1.1q=-0.4q-5.3 | | .75+z=.83 | | 45=36x | | 2(x-4)+7(x+2)= | | 7(2-r)-2(3r+8)=24 | | d-2.8/0.2=-14 | | 3x-x+15=41 | | -7y+7=-8y+4 | | 6(2-5)-8= | | 4z=3z+z | | S=p-0.35p | | 6(x-y)-8= |